2014
DOI: 10.1038/nrurol.2014.22
|View full text |Cite
|
Sign up to set email alerts
|

Urological complications of illicit drug use

Abstract: Illicit drug use is prevalent worldwide; over 24 million people are estimated to have used recreational drugs during the past month in the UK and USA alone. Illicit drug use can result in a wide spectrum of potential medical complications that include many urological manifestations. To ensure optimal care and treatment, urologists need to be cognizant of these complications in their patients, particularly among youths. Ketamine uropathy is thought to affect over one-quarter of ketamine users and can lead to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 130 publications
0
27
0
Order By: Relevance
“…Experimental animal studies have shown that by binding to CB1 and CB2 in Leydig cells and Sertoli cells of the testes, levels of testosterone, follicle-stimulating hormone and luteinizing hormone are affected, as is the survival of Sertoli cells (2831). Aberration in both steroid hormone levels and gonadotropin levels suggests that cannabinoids may cause a general perturbation to the hypothalamic-pituitary-gonadal axis which could result in tumorigenesis (32). Much more research in this area, including timing of exposure, is required, however.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental animal studies have shown that by binding to CB1 and CB2 in Leydig cells and Sertoli cells of the testes, levels of testosterone, follicle-stimulating hormone and luteinizing hormone are affected, as is the survival of Sertoli cells (2831). Aberration in both steroid hormone levels and gonadotropin levels suggests that cannabinoids may cause a general perturbation to the hypothalamic-pituitary-gonadal axis which could result in tumorigenesis (32). Much more research in this area, including timing of exposure, is required, however.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, although MDMA, marijuana, and hypnotics use was significantly associated with LUTS in the univariate analysis, the association was not observed in the multivariate analysis. Urological complications associated with by illicit drug use are being increasingly addressed . Furthermore, neurogenic bladder and chronic urine retention were previously reported in a case of chronic MDMA use; the mechanism of the association between chronic MDMA use and neurogenic bladder and chronic urine retention may be chronic upregulation of the sympathomimetic influence on the urinary bladder, inhibition of parasympathetic control, persistent urinary sphincter contraction, and detrusor muscle dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine use has been associated with symptoms including severe pain, frequency, haematuria and dysuria (Tsai and Kuo, 2015). The use of some psychoactive substances, mainly stimulants such as MDMA and amphetamine are associated with urinary retention (Skeldon andGoldenberg, 2014 andSelius andSubedi, 2008).…”
Section:  Medicationmentioning
confidence: 99%